Higher levels of psychological burden and alterations in personality functioning in Crohn’s disease and Ulcerative Colitis - Engel, Felicitas; Berens, Sabrina; Gauss, Annika; Schaefert, Rainer; Eich, Wolfgang; Tesarz, Jonas (Frontiers in psychology, 2021)
Aims: Is there evidence for increased psychological distress and alterations in personality functioning in patients with Crohn's disease (CD) and ulcerative colitis (UC) compared to healthy controls (HC)? Background: In patients with Crohn's disease (CD) and ulcerative colitis (UC), perceived stress is closely associated with changes in disease activity. The stress response is influenced by psychological burden and personality functioning, but only little is known about these factors in inflammatory bowel diseases. Study: A total of 62 individually patients with an endoscopic ensured CD/UC without remission (n=31 per group) and 31 HC were included. Patients with an active CD/UC and HC were individually matched (n=93, 31 per group) for age, sex, education and disease acitivty. Depression and anxiety were assessed to evaluate the effect of psychological burden. Personality functioning was measured by validated questionnaires for psychodynamic structural characteristics, mentalization and attachment. Results: Levels of depressivion and anxiety were higher in CD/UC-patients than in HC with large effect sizes. Comparing personality functioning in CD/UC with HC, psychodynamic structural characteristics differed between CD/UC and HC with medium effect sizes, with structural differences occurring primarily in the domain of self perception and regulation. Only minor differences were found regarding mentalization and attachment. CD and UC differed only with small effect sizes. Conclusion: Our data show that compared to HC, patients with CD/UC are characterized by a higher level of psychological burden and structrual alterations in the domain of self.